Teacher Support as Determinant of Academic Achievement - Sharma, Dr. Gouri (IJRDO- Journal of Educational Research, 2016)
Measuring achievement is a major part of the learning process and informs educators of student talent and progress toward educational goals. Today’s modern society expects each one to be a high achiever. It has become an indicator of a child’s future. Parents, teachers and higher authorities concerned with effective academic performance of the students. Present study aimed to investigate the effect of teacher support locale and sex on academic achievement. For this purpose initially larger number of student Studying in government schools of Rajnandgaon district of Chhattisgarh state were selected out of which 646 students were retained as final sample. To measure the academic achievement of the student, over all marks obtained by the student in different subjects (viz-Hindi, English, Mathematics, Science, & Social Science) in class 10th board examination was used. The dependent variable of the study was academic achievement and independent variables were teacher support locale and sex. To analyze the data descriptive statistics, and ANOVA technique is used. The ANOVA analysis reveals that teacher support and locale affect independently as well as jointly to academic achievement whereas role of sex was not found to be significant.